A Java Framework for Multi-agent Systems - Avancini, Henri (2000)
The complexity of distributed systems (multi-agent systems in particular) involves the design and coordination of many entities (called agents). This activity is not trivial and there is not a standard way to do this. So, it is desirable to have tools for reusing previous designed components and relations between them. Frameworks allow design and code to be reused. Intelligent agents cover a big amount of application domains but we can detect an important set of common characteristics that can be abstracted for reusing. This paper presents a framework for multi-agent systems (FraMaS) composed by these common characteristics. FraMaS is used to design agents that have capabilities for perceiving environment, communicating, and deliberating about what to do next.